2006
DOI: 10.1007/s10661-006-9496-y
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Leaching Test Framework for Coal Fly Ash Accounting for Environmental Conditions

Abstract: Fly ash from coal combustion contains trace elements which, on disposal or utilisation, may leach out, and therefore be a potential environmental hazard. Environmental conditions have a great impact on the mobility of fly ash constituents as well as the physical and chemical properties of the fly ash. Existing standard leaching methods have been shown to be inadequate by not representing possible disposal or utilisation scenarios. These tests are often criticised on the grounds that the results estimated are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…According to previous studies, some elements such as Ca, Cr and Mg are reported to the surface of the fly ash particles, while Al, Si, K, Pb and many other trace elements are distributed throughout the particle [40,41]. Most of the cationic elements including Mg, Cu, Mn and Ni, show lower leaching rates due to their chemical behavior in solution below pH 10.…”
Section: Results Of the Toxicity Test Proceduresmentioning
confidence: 98%
See 1 more Smart Citation
“…According to previous studies, some elements such as Ca, Cr and Mg are reported to the surface of the fly ash particles, while Al, Si, K, Pb and many other trace elements are distributed throughout the particle [40,41]. Most of the cationic elements including Mg, Cu, Mn and Ni, show lower leaching rates due to their chemical behavior in solution below pH 10.…”
Section: Results Of the Toxicity Test Proceduresmentioning
confidence: 98%
“…The solubility of these elements tends to increase at pH levels above and below 7. Solubility of Cr increases with increasing pH for pH levels over 7 and decreases in strong basic conditions (pH > 11) [38][39][40].…”
Section: Results Of the Toxicity Test Proceduresmentioning
confidence: 99%
“…In the light of the pronounced mobility reported throughout the literature, special consideration should be given to these elements in disposal FIGURE CAPTIONS Figure 1. General trends in the leaching behaviour of selected elements vs pH after Chandler et al (1997), de Groot (1989, Dubikova et al (2006), Jankowski et al (2004), Jones (1995), Moreno et al (2005), van der Sloot (1990) and Zandi and Russell (2007). …”
Section: Discussionmentioning
confidence: 99%
“…A detailed discussion on the worldwide standard leaching tests is out of the scope of this study and can be found elsewhere (Chandler et al, 1997;Kim, 2002;van der Sloot, 1997;Zandi and Russell, 2007).…”
Section: Leaching Protocols and Regulationsmentioning
confidence: 99%
See 1 more Smart Citation